Clinical highlights from the 2011 ERS Congress in Amsterdam - Spruit, Martijn; Herth, Felix; Ley, Sebastian (The European respiratory journal, 2012)
This article reports on selected papers pertinent to the most important clinical problems in the field of respiratory medicine. Expert authors from the Clinical Assembly of the European Respiratory Society (ERS) have selected updated reports related to presentations given at the 2011 ERS Annual Congress, which was held in Amsterdam (the Netherlands) and attended by more than 20,000 participants. The hot topics and selected abstracts from the scientific groups of the Clinical Assembly are discussed here in the context of recent literature.